Synthesis Of Silver Nanoparticles With Antibacterial Activity Using The Lichen Parmotrema Praesorediosum - Siti Noor Adnalizawati Adnan; Ropisah Mie; Mohd Wahid Samsudin; Laily B Din; Azizan Ahmad; Nazlina Ibrahim (Dovepress, 2024)
Development of a green chemistry process for the synthesis of silver nanoparticles has become a focus of interest. This would offer numerous benefits, including ecofriendliness and compatibility for biomedical applications. Here we report the synthesis of silver nanoparticles from the reduction of silver nitrate and an aqueous extract of the lichen Parmotrema praesorediosum as a reductant as well as a stabilizer. The physical appearance of these silver nanoparticles was characterized using ultraviolet-visible spectroscopy, electron microscopy, energy-dispersive spectroscopy, and X-ray diffraction techniques. The results show that silver nanoparticles synthesized using P. praesorediosum have an average particle size of 19 nm with a cubic structure. The antibacterial activity of the synthesized silver nanoparticles was tested against eight micro-organisms using the disk diffusion method. The results reveal that silver nanoparticles synthesized using P. praesorediosum have potential antibacterial activity against Gram-negative bacteria.